Study of the Performance Thermal Forced Unglazed Solar Air Collector - Jameel Shareef, Amir (Anbar Journal of Engineering Sciences, 2012)
An experimental study is achieved to study the thermal performance of forced unglazed solar air collector supplied with perforated absorber flat plate. The study is carried under Iraqi circumferences in Al-Ramadi city .The collector is inclined (90o) on horizontal for the simplicity of setting such type of collector on the wall building and minimize its weight. The measurement is recorded on Winter season for two sunny days and two cloudy days in (January 2012). The results show that its possible to use this type of collectors for heating in Winter time because the maximum out air temperature reach to (34oC) when ambient air temperature at (17oC) in sunny days. A good agreement is shown with the published studies Finally its obtained a good effectiveness for perforated flat plate absorber with high system efficiency.